Contribution of legume-N by nodulated groundnut for growth of maize on an acid soil - Anuar, A.R.; Shamsuddin, Z.H.; Yaacob, O. (1995)
A series of glasshouse and field experiments was undertaken to test the hypothesis that intensive cropping of a selected groundnut cultivar inoculated with a compatible and highly effective strain of Bradyrhizobium could contribute substantial amounts of N to the succeeding cereal crops. In the glasshouse experiment, the Bradyrhizobium (strain CB756)-groundnut cultivar (V13) combination produced maximum pod yield and N concentration in the haulm on unlimed and limed soil. An equivalent of 77 kg N ha-1 without lime and 105 kg N ha-1 when limed was estimated to be returned to the soil as legume-N through the groundnut residue. This symbiotic combination was used in a limed (4 t ground magnesium limestone ha-1) crop rotation field experiment to estimate the amount of N contributed by groundnut residue as measured by the yield of maize. After 1-3 successive legume crops, an estimated 20-56 kg N ha-1 were contributed to the subsequent maize crops. This accounted for 31 and 37% recovery of the respective total legume-N. © 1995.